Peculiarities of Civil Education of Students - Inna Shorobura (Pedagogical Discourse, 2013)
The author of the article pays attention to the peculiarities of civil education of students. It is mentioned what features of character should modern pedagogical workers possess and what professional knowledge, abilities and skills they should have for civil education of students. It is indicated to the structural components of civil education as well as to the peculiarities of policultural education at the present period of time.